Multiple apoptotic caspase cascades are required in nonapoptotic roles for Drosophila spermatid individualization. - Jun R Huh; Stephanie Y Vernooy; Hong Yu; Nieng Yan; Yigong Shi; Ming Guo; Bruce A Hay (PLoS Biology, 2004)
Spermatozoa are generated and mature within a germline syncytium. Differentiation of haploid syncytial spermatids into single motile sperm requires the encapsulation of each spermatid by an independent plasma membrane and the elimination of most sperm cytoplasm, a process known as individualization. Apoptosis is mediated by caspase family proteases. Many apoptotic cell deaths in Drosophila utilize the REAPER/HID/GRIM family proapoptotic proteins. These proteins promote cell death, at least in part, by disrupting interactions between the caspase inhibitor DIAP1 and the apical caspase DRONC, which is continually activated in many viable cells through interactions with ARK, the Drosophila homolog of the mammalian death-activating adaptor APAF-1. This leads to unrestrained activity of DRONC and other DIAP1-inhibitable caspases activated by DRONC. Here we demonstrate that ARK- and HID-dependent activation of DRONC occurs at sites of spermatid individualization and that all three proteins are required for this process. dFADD, the Drosophila homolog of mammalian FADD, an adaptor that mediates recruitment of apical caspases to ligand-bound death receptors, and its target caspase DREDD are also required. A third apoptotic caspase, DRICE, is activated throughout the length of individualizing spermatids in a process that requires the product of the driceless locus, which also participates in individualization. Our results demonstrate that multiple caspases and caspase regulators, likely acting at distinct points in time and space, are required for spermatid individualization, a nonapoptotic process.